2016
DOI: 10.1007/s00464-016-4946-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefits and oncologic equivalence of self-expandable metallic stent insertion for right-sided malignant colonic obstruction

Abstract: Stent insertion appears to be safe and feasible in patients with right-sided colonic malignant obstruction. It facilitates minimally invasive surgery and may result in better short-term surgical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 20 publications
1
32
0
2
Order By: Relevance
“…Recent studies have revealed that colonic stenting, as a bridge to elective surgery, can contribute to not only an increased rate of laparoscopic surgery but also to a decreased conversion rate [25, 26]. Although most of the present patients with preoperative ileus were managed by TPN instead of oral intake, intraoperative bowel distension was not fully improved.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have revealed that colonic stenting, as a bridge to elective surgery, can contribute to not only an increased rate of laparoscopic surgery but also to a decreased conversion rate [25, 26]. Although most of the present patients with preoperative ileus were managed by TPN instead of oral intake, intraoperative bowel distension was not fully improved.…”
Section: Discussionmentioning
confidence: 95%
“…Repici et al reported that the success rate for SEMS insertion for right-sided malignant colonic obstruction was 95% (20/21), with resolution of obstructive symptoms and no immediate complications in 85% of cases (17/20) [16]. Similarly, another recent study reported a success rate of 87.5% and symptom relief rate of 100% with no immediate complications [17]. In the present study, re-obstruction as a long-term complication occurred in only one patient.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Amelung et al [22] found that patients treated with SEMS were less likely to require a temporary stoma, although there were no signi cant differences in the morbidity and mortality rates between the SEMS and ES groups. Another study reported shorter postoperative hospital stays and time to resume oral food intake in the SEMS group, suggesting better recovery from surgery [17]. However, there is a lack of multicentre randomised controlled trials to con rm the advantages in terms of morbidity or mortality of the use of colon stenting as a bridge to surgery vs ES for patients with MORC.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we reported our experience of the endoscopy-guided only method for SEMS insertion. Since gastrointestinal endoscopy is an image-guided procedure, the therapeutic strategy can be made according to [6,10], by providing some radiological evidence. In our practice, determinations are made by reviewing images of CT scans.…”
Section: Discussionmentioning
confidence: 99%